2012
DOI: 10.1075/eww.33.2.03ofo
|View full text |Cite
|
Sign up to set email alerts
|

I own this language that everybody speaks

Abstract: Based on interviews conducted in ten Catholic churches of the Ghanaian capital, Accra, the paper offers a profile of English use in Ghana and reports on the attitudes of Ghanaians toward English as the official language of their country. The results reveal the influential role English plays in the different settings of Ghanaian communication as well as the high esteem afforded to the English language by the majority of Ghanaian respondents. Most of them cited the numerous benefits that English, as a language o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Consistent with previous studies on language attitude and motivation, the present study found that the participants hold favorable attitude towards English because they are instrumentally motivated (Al-Haq 2000, Lai 2005Hohenthal 2003, Majumder 2005, Shirbagi 2010, Ofori & Albakry 2012. Five themes emerged from the semi-structured interviews.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with previous studies on language attitude and motivation, the present study found that the participants hold favorable attitude towards English because they are instrumentally motivated (Al-Haq 2000, Lai 2005Hohenthal 2003, Majumder 2005, Shirbagi 2010, Ofori & Albakry 2012. Five themes emerged from the semi-structured interviews.…”
Section: Discussionsupporting
confidence: 87%
“…These themes seem to corroborate what previous studies found as regards instrumental motivation in language learning. The participants consider English as an indicator of competence (Lai 2009), a vehicle for communication (Ofori & Albakry 2012), an edge in the workplace (Hohenthal 2003, Majumder 2005, Lai 2009) and a global/international status marker (Majumder 2005, Shirbagi 2010). These themes are consistent with Kachru's (1992) definition of instrumental motivation, which is essentially 'utilitarian' in nature and in which a language is seen as a linguistic tool and not an instrument for cultural integration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ofori and Albakry (2012) relate some striking remarks from Ghanaian respondents about locally appropriated English, not least the article's eponymous interview quote, “I own this language that everybody speaks” (p. 173). But globally dominant languages, so tainted with the stench of colonial injustice, seem irredeemably barred from prevailing discourses of LHR, even in these localized varieties (Mufwene, 2017, pp.…”
Section: Linguistic Human Rights (And Its Discontents)mentioning
confidence: 99%
“…Integrativeness or integrative motivation in learning a second language (henceforth L2) was first introduced by Gardner and Lambert (1959). The extant literature on language learning motivation would suggest that a considerable body of work along this line focused on identifying various groups of learners in various levels and contexts according to whether their L2 motivation was instrumental (Al-Haq, 2000;AlTamimi & Shuib, 2009;Hohenthal, 2003;Lai, 2005Lai, , 2009Majumder, 2005;Shirbagi, 2010;Ofori &Albakry, 2012;Quinto, 2015), i.e., language learning is utilitarian in nature and language is acquired as a linguistic tool and not as an instrument of cultural integration (Kachru, 1992); or integrative (Benson, 1991;El-Dash & Busnardo, 2001;Hogan-Brun & Ramoniene, 2004, i.e., language learning towards linguistic cultural integration with a specific group of speakers (Prator, 1968in Kachru, 1992.…”
Section: Introductionmentioning
confidence: 99%